2002
DOI: 10.1159/000066608
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen chromosomal localizations and an update of the cytogenetic map of the rabbit

Abstract: In order to improve the informativeness of the cytogenetic map of the rabbit genome, fourteen markers were regionally mapped to individual chromosomes. The localizations comprise eleven gene loci (PRLR, GHR, HK1, ACE, TF, 18S+28S rDNA, CYP2C4, PMP2, TCRB, ALOX15 and MT1) and three microsatellite loci (Sat13, Sol33 and D1Utr6). Five of the genes contain known microsatellite sequences. To achieve these localizations, homologous and heterologous small insert clones, and clones from a rabbit Bacterial Artificial C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…However, we localized CALR on OCU10 and GHR on OCU11. As previously discussed by Zijlstra et al (2002), we confirm that OCU10 and OCU11 are interchanged in the study by Korstanje et al (1999). Concerning DNASE1, located on HSA16p13.3, we have localized it on the p arm of OCU6 and not on the q arm as expected from Korstanje and co-workers (1999).…”
Section: Fish Localization Of 23 Chromosome-specific Genes On Gand R-supporting
confidence: 90%
See 3 more Smart Citations
“…However, we localized CALR on OCU10 and GHR on OCU11. As previously discussed by Zijlstra et al (2002), we confirm that OCU10 and OCU11 are interchanged in the study by Korstanje et al (1999). Concerning DNASE1, located on HSA16p13.3, we have localized it on the p arm of OCU6 and not on the q arm as expected from Korstanje and co-workers (1999).…”
Section: Fish Localization Of 23 Chromosome-specific Genes On Gand R-supporting
confidence: 90%
“…IGF2, TGFA, IGF1, DNASE1, F7, CYB5, CALR, SLC2A1, AHSG, PIGR, LIPC, TGFB3, NOS1 and SRY. Eight genes, TNF (Rogel-Gaillard et al, 2001), CSN1 (Pauloin et al, 2002), PMP2, MT1A, TRB GHR, CYP2C4 and ALOX15 (Zijlstra et al, 2002), have been previously mapped and their localization is confirmed here on either G-or Rbanded chromosomes. Finally the HPRT1 gene, which had been previously assigned to OCUX by somatic cell hybrid analysis (Echard et al, 1981), is now regionally mapped to Xq23.…”
Section: Fish Localization Of 23 Chromosome-specific Genes On Gand R-supporting
confidence: 64%
See 2 more Smart Citations
“…Later, chromosomal analyses using cultured cells (Nichols et al 1965;Ray and Williams 1966;Issa et al 1968) confirmed the pioneering observations made by Painter. Finally, it has been shown that chromosomes 13, 16, and 20 (telomeric p arm) and 21 (telomeric q arm) bear the nucleolar organizer regions (Martin-DeLeon 1980;Zijlstra et al 2002). The banding patterns of rabbit chromosomes have been described in detail by several groups: G-banded metaphase chromosomes (Echard 1973;Chan et al 1977;Ford et al 1980; Committee for Standardized Karyotype of Oryctolagus cuniculus 1981), G-, Q-, and R-banded metaphase chromosomes (Hageltorn and Gustavsson 1979), G-banded late prophase chromosomes (Yerle et al 1987), R-banded prometaphase chromosomes (Poulsen et al 1988;Rønne et al 1993, Rønne 1995, and G-and R-banded midmetaphase chromosomes .…”
Section: Cytogenetics the Rabbit Karyotypementioning
confidence: 99%